New issues in the Uruguay Round and beyond. - HOEKMAN, Bernard M. (1993)
Provides a brief overview of what was achieved on the new issues of trade related investment measures (TRIMs), trade-related intellectural property rights (TRIPs), and trade in services. Notes that the expansion of the agenda to include the new issues has been associated with substantial progress in a number of 'old' GATT issues.